Aramid Nanomaterials of Various Morphologies: Preparation and Mechanical Property Enhancement - Dong, Congcong; Guo, Peng; Yuan, Yue; Sun, Changmei; Qu, Rongjun; Ji, Chunnuan; Zhang, Ying; Wang, Ying (Frontiers in Chemistry, 2020)
Aramid nanofibers (ANFs) are a novel type of promising nanoscale building blocks for high-performance nanocomposites. Conventionally, ANFs are used to composite with polymers containing polar groups such as –OH and –NH2 since those polymers can interact with the amide groups in ANFs through polar-polar interaction such as hydrogen bonding. In this study, ANFs were derivatized with non-polar alkyl groups including ethyl, octyl and dodecyl groups and used as a performance-enhancing additive to polyvinyl chloride (PVC) with weak polarity. Interestingly, it was observed that the morphologies of the resulting alkyl-derivatized aramid nanomaterials (R-ANMs) varied significantly including nanofibers, nanobranches, nanosheets, and nanospheres, all of which depended on the degree of substitution (DS) and the chain length of the alkyl group. As an additive, R-ANMs improved the Young’s modulus, toughness and yield strength of the PVC films. This study proves the concept that ANFs can be used to composite weakly polar or nonpolar polymers.